Pelaksanaan Pembelajaran Diferensiasi Sebagai Solusi Beragaman Peserta Didik di Sekolah Dasar - Ali, Aisyah; S, Chelsi Yuliana; Sukmawati, Sukmawati; Ristiani, Ria; Rusli, Tiffany Shahnaz (Universitas Negeri Makassar, 2024)
This research focuses on differentiation learning carried out by teachers at SD Negeri Inpres VIM I Kotaraja Jayapura City, Papua Province as a demand for curriculum changes. The background of the problem comes from the difficulty of identifying learning needs, learning styles, interests of students from different social backgrounds. This requires teachers to be able to create learning that suits the needs and abilities of each student. In this case, implementing differentiated learning can be a solution to overcome student diversity. The expected result of this research is a better understanding of the application of differentiated learning and improving the quality of learning at SD Negeri Inpres VIM I Kotaraja Jayapura City, Papua Province through differentiated learning. In addition, the recommendations of this research are to increase the application of differentiated learning in elementary schools, and its availability. source of information for teachers and other researchers.